Genotype x Environment Interaction and Yield Stability Analysis of Some Chickpea (Cicer arietinum L.) Genotypes across Different Environments in Sudan - E. A. Hamza, Fatih; A. Mohamed, Amel; A. Tambal, Hassan; M. O. Mahagoub, Rasha; Elmahi Mohamed, Omyma; Haroun M. Adam, Abubaker (Journal of Agronomy Research, 2023)
Genotype by environment (GE) interaction is considered to be among the major factors limiting the efficiency of breeding programs.Five chickpea genotypes were evaluated to study their adaptability and stability in eight environments of Sudan. The experiments were carried out in randomized complete block design (RCBD) with four replications in four locations in over two years (2017/2018 and 2018/2019).Stability was estimated using additive main effects and multiplicative interaction (AMMI) model.A Combined analysis of variance showed significant effects of genotypes, locations, years and their interactions on seed yield. Mean seed yield ranged between 1.88 and 1.45 t ha-1 for the genotypes FLIP 08-59 C and FLIP 09-187 C, respectively. The genotype FLIP 08-59 C gave the highest average seed yield and out-yielded the two checks, Shiekh Mohamed and Burgeig by 9.5% and 10.1%, respectively. The newly introduced (FLIP 08-59 C) showed non- significant differences in earliness as compared to the other two standard checks resistant to fusarium wilt disease and with good seed weight. The statistical analysis showed that genotype (G), environment (E) and their interaction (GEI) had highly significant (P ≤ 0.001) effect on seed yield. It also revealed that environmental differences accounted for 90.2% of the total variation. The results of data analysis displayed that the percentages of seed yield by environment, genotype and genotype environment interaction were 90.2%, 3.6% and 6.3%, respectively. The IPCA 1 and IPCA 2 axes (Principal Components) were highly significant P ≤ 0.001). The model for seed chickpea yield stability (the Additive Main Effect and Multiplicative Interaction (AMMI) model) showed that the G1 (FLIP 08-59 C) was adapted, high yielding and considered as stable genotype for Gezira, River Nile and Northern States of Sudan. In addition, this genotype is early flowering with non-significant differences in earliness as compared to the two checks and with good seed weight. Therefore, the above mentioned genotype FLIP 08-59 C could be recommended as commercially stable and high yielding cultivar and/or incorporated as breeding stocks in any future breeding programs aiming to produce high yielding genotypes of chickpea.
Keywords: Chickpea; Genotypes; Seed Yield; AMMI; Fusarium Wilt